Hope to die - Patterson, James, 1947- (Patterson, James, 1947- Alex Cross series., 2014)
"Detective Alex Cross is being stalked by a psychotic genius, forced to play the deadliest game of his career. Cross's family--his loving wife Bree, the wise and lively Nana Mama, and his precious children--have been ripped away. Terrified and desperate, Cross must give this mad man what he wants if he has any chance of saving the most important people in his life. The stakes have never been higher: What will Cross sacrifice to save the ones he loves?" --